Un ponte tra università e mondo del lavoro per l'inclusione e la vita indipendente - Pavone, Marisa; ARENGHI, Alberto; BORGONOVI, ELIO; Ferrucci, Fabio; Genovese, Elisabetta; Pepino, Alessandro (Aziende pubbliche e imprenditorialità sociale (APIS), 2022)
The book is a collection of selected papers presented during the conference "bridge between university and workplace for inclusion and independent life" that had been hold on October 25, 2021. It start with a declaration on "the culture of inclusive work: visions, strategies, proposals" signed by all the rectors' delegates for students with disabilities and learning disorders and it is organized into three parts. The first concerns theories and general issues related to inclusion. The second deals with the policies and good practices of universities to support graduates with disabilities in the search of employment. The third includes cases and life experiences of expected inclusion. The logic of the book can be summarized as follows. From teaching too learning and from learning to employability the road map for universities. From employability to employment is the bridge between universities and enterprises, public administration and not for profit organizations. From employment to inclusion is what the people hiring institutions must and should do to realize inclusion in the perspective of wellbeing of employees and to get a competitive advantage.